1995
DOI: 10.2466/pms.1995.80.3.735
|View full text |Cite
|
Sign up to set email alerts
|

Gait Disturbance of Patients with Vascular and Alzheimer-Type Dementias

Abstract: The gaits of 15 patients with senile dementia of the Alzheimer type and 15 with vascular dementia were compared with those of 15 healthy control subjects. Patients with senile dementia showed significantly slower velocity and shorter step length than the healthy controls, and those with vascular dementia exhibited a reduction on these two variables relative to patients with senile dementia of the Alzheimer type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
30
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 15 publications
5
30
0
Order By: Relevance
“…In spite of this, step length at self-selected speed was a bit longer than values presented by others [7,25,26,29] . Cadence was in agreement with data from Visser [7] and Tanaka et al [31] , even though the patients of Tanaka et al had shorter step length.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In spite of this, step length at self-selected speed was a bit longer than values presented by others [7,25,26,29] . Cadence was in agreement with data from Visser [7] and Tanaka et al [31] , even though the patients of Tanaka et al had shorter step length.…”
Section: Discussionsupporting
confidence: 87%
“…All our patients walked without any assistive device and were slightly faster at both speeds compared with others [7,25,26,31] . In spite of this, step length at self-selected speed was a bit longer than values presented by others [7,25,26,29] .…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…A study conducted with 30 participants with AD, vascular dementia (VD) and cognitively preserved elderly people showed a significant decrease in stride length and speed when compared to a control group 28 . The authors concluded that stride length was a more important predictor of the walking pattern than cadence and speed and that this finding may be directly related to changes in blood flow in the frontal region of Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with many other neurodegenerative diseases, such as Parkinson's disease, subcortical arteriosclerotic encephalopathy, progressive supranuclear palsy (PSP), and corticobasal degeneration, may develop hypokinetic gait during the disease progression [4,35,37] ■ Abstract Background and purpose Although gait disturbance is an important feature of idiopathic normal pressure hydrocephalus (NPH), only tentative theories have been offered to explain its pathophysiology. It has been suggested that the mesencephalic locomotor region is the anatomical substrate for the development of the hypokinetic NPH gait.…”
mentioning
confidence: 99%